Relationship between amount of variability in eye motion and performance in simulated sailing - Menayo Antúnez, R.; Manzanares Serrano, A.; Segado, F.; Martinez, M. (European Journal of Human Movement, 2016)
The start regatta is a key moment in the race. The aim of this research was to know the relationship between variability of eye motion and the performance achieved in simulated regatta start. Thirty young sailors were distributed among three performance groups: Optimum Performance Group -OPG- (N=11), Middle Performance Group -MPG- (N=13) and Low Performance Group-LPG-(N=7), considering the distance above or below the start line. A system of measurement, which integrates the VSail-Trainer® simulator and the Eye Tracking SystemTM, was used. The vertical and horizontal positions of boat at start, the velocity of boat, and the mean velocity on start regatta were measured. The standard deviations of displacement and velocity of eyes were registered. From the results it is emphasized that OPG got a closer position to the start line than MPG and LPG (p = .001; d = 1.29 / p = .001; d = 3.90). Best located sailors at the start line show a negative correlation between boat mean velocity and the variability on eye velocity (r = -.718; p = .013). In conclusion a greater amount of variability in eye motion is related to a worse performance at the start regatta.